2023
DOI: 10.1029/2022jd036866
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin‐Helmholtz Billows in the Troposphere and Lower Stratosphere Detected by the PANSY Radar at Syowa Station in the Antarctic

Abstract: Kelvin-Helmholtz (K-H) instability is shear instability that occurs in a stably stratified fluid with strong vertical shear of the horizontal winds. It is well known that a necessary condition for K-H instability is that the Richardson number ( 𝐴𝐴 Ri ) must be <0. 25 (e.g., Miles & Howard, 1964;Scorer, 1969). The Richardson number can be estimated as follows: 𝐴𝐴 Ri = 𝑁𝑁 2 ∕|d𝑼𝑼 ∕d𝑧𝑧| 2 , where 𝐴𝐴 𝐴𝐴 2 is the square of the buoyancy (Brunt-Vӓisӓlӓ) frequency and 𝐴𝐴 |d𝑼𝑼 ∕d𝑧𝑧| is the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Recent studies based on observations from a Mesosphere-Stratosphere-Troposphere (MST) radar at Syowa Station provide new insights into GWs in the Antarctic region, including their momentum fluxes (Sato et al, 2014(Sato et al, , 2017Shibuya et al, 2017), wave parameters (Minamihara et al, 2018), and their intermittency (Minamihara et al, 2020). The estimated turbulent energy dissipation rate is also used to examine the relation between GWs and turbulence (Kohma et al, 2019(Kohma et al, , 2021Minamihara et al, 2023). Although there have been several studies based on numerical simulations of GWs observed over Syowa Station (e.g., Minamihara et al, 2023;Shibuya et al, 2017), they are based on calculations with horizontal grid spacings of 2.8 km or larger.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies based on observations from a Mesosphere-Stratosphere-Troposphere (MST) radar at Syowa Station provide new insights into GWs in the Antarctic region, including their momentum fluxes (Sato et al, 2014(Sato et al, , 2017Shibuya et al, 2017), wave parameters (Minamihara et al, 2018), and their intermittency (Minamihara et al, 2020). The estimated turbulent energy dissipation rate is also used to examine the relation between GWs and turbulence (Kohma et al, 2019(Kohma et al, , 2021Minamihara et al, 2023). Although there have been several studies based on numerical simulations of GWs observed over Syowa Station (e.g., Minamihara et al, 2023;Shibuya et al, 2017), they are based on calculations with horizontal grid spacings of 2.8 km or larger.…”
mentioning
confidence: 99%
“…The estimated turbulent energy dissipation rate is also used to examine the relation between GWs and turbulence (Kohma et al, 2019(Kohma et al, , 2021Minamihara et al, 2023). Although there have been several studies based on numerical simulations of GWs observed over Syowa Station (e.g., Minamihara et al, 2023;Shibuya et al, 2017), they are based on calculations with horizontal grid spacings of 2.8 km or larger.…”
mentioning
confidence: 99%